Analysis of Severity and Anatomical Distribution of Diabetic Foot Ulcers-A Single Unit Experience - Ambegoda, A.L.A.M.C.; Wijesekera, J.R.; Panditharathne, K.I.; Gamage, R.T.; Mudalige, O.M.D.C.S.; Piyasiri, M.D.R.M. (My University, 2016)
Diabetes is the commonest cause of foot ulceration in developing countries leading to severe morbidity and mortality. The main aim of this study was to assess anatomical distribution of diabetic foot lesions, categorize it according to Wagner wound grading, find any association between smoking packs years and the severity of the foot lesions. Also to assess the relationship between the bony deformities and anatomical distribution of the ulcers. This was a cross sectional descriptive study conducted in a casualty surgical unit in a tertiary care teaching hospital for a period of 4 months. 91 diabetic patients with a diabetes related foot lesion were enrolled after simple randomization. Pretested interviewer administered questionnaire was used to gather data. Variety of soft tissue and bony changes of diabetic foot were assessed. Lesions were classified according to Wagner classification. Data was analysed using Epidata software. From the 91 participants, 55 (61 %) were males and 36 (39%) females. Mean age was at 60. 12 ± 10. 19 years. Median diabetes duration was 10 years (Interquartile range = 4.25 – 16.75). Wagner grade 1, 2, 3, 4 and 5 were 17.7%, 40.65%, 28.8%, 13.3% and 0% respectively. Commonest ulcer location was margins of foot (31.87%). There was no statistically significant association between the pack years of cigarette smoking males and severity of foot lesions (Spearman’s rank correlation coefficient = - 0.037, p = 0.82). Patients with claw and hammer toe deformities had their ulcers located in fingertips and toes (p = 0.0185). But there was no statistically significant association with flat foot deformity and ulcer distribution on any particular anatomical area in the foot (p = 0.0511). In conclusion there is a statistically significant association between toe deformities and ulcer occurrence in finger tips. No significant correlation between severity of smoking and severity of foot lesions among males is present.
Keywords: Diabetic ulcers; Diabetic foot lesions; Wagner classification; Dlcer distribution